Association of Blood Pressure Level With Left Ventricular Mass in Adolescents: SHIP AHOY. Issue 3 (September 2019) - Urbina, Elaine M.; Mendizábal, Brenda; Becker, Richard C.; Daniels, Steve R.; Falkner, Bonita E.; Hamdani, Gilad; Hanevold, Coral; Hooper, Stephen R.; Ingelfinger, Julie R.; Lanade, Marc; Martin, Lisa J.; Meyers, Kevin; et al.
Abstract : Hypertension is associated with left ventricular hypertrophy (LVH), a risk factor for cardiovascular events. Since cardiovascular events in youth are rare, hypertension has historically been defined by the 95th percentile of the normal blood pressure (BP) distribution in healthy children. The optimal BP percentile associated with LVH in youth is unknown. We aimed to determine the association of systolic BP (SBP) percentile, independent of obesity, on left ventricular mass index (LVMI), and to estimate which SBP percentile best predicts LVH in youth. We evaluated SBP, anthropometrics, and echocardiogram in 303 adolescents (mean age 15.6 years, 63% white, 55% male) classified by SBP as low-risk (L=141, <80th percentile), mid-risk (M=71, 80–<90th percentile), or high-risk (H=91, ≥90th percentile) using the mean of 6 measurements at 2 visits according to the 2017 guidelines. Logistic regression was used to determine the sensitivity and specificity of various SBP percentiles associated with LVH. Results: BP groups did not differ by age or demographics but differed slightly by body mass index. Mean BP, LVMI, and prevalence of LVH increased across groups (BP: L=111/75, M=125/82, and H=133/92 mm Hg; LVMI: L=31.2, M=34.2, and H=34.9 g/m 2.7 ; LVH: L=13%, M=21%, H=27%, all P <0.03). SBP percentile remained a significant determinant of LVMI after adjusting for covariates. The 90th percentile for SBP resulted in the best balance between sensitivity and specificity for predicting LVH (LVMI≥38.6 g/m 2.7 ). Abnormalities in cardiac structure in youth can be found at BP levels below those used to define hypertension. Abstract : Supplemental Digital Content is available in the text.